Labu ACU: an innovation for commercialization of Malaysian pottery heritage - Haron, Hamdzun; Yunos, Nasruddin; Zainal Amri, Norhasliyana Hazlin; Ali Yasin, Siti Maryam (IAEME, 2018)
Labu Sayong (A water pitcher from earthenware clay) is also known as Labu Picit from the state of Perak. It is one of Malay heritage crafts. This pottery craft has its own special feature. The water kept inside the clay pitcher is colder than usual and is said to be refreshing to the body when consumed. Labu Sayong was an adaptation of a gourd and was a symbol of the intellectual of Malay in the past. It is produced using several traditional processes in stages and took quite a long time to complete. This problem can contribute to its extinction and therefore many entrepreneurs are changing their direction towards a new innovation in the clay pitcher manufacturing process using slip casting technique. This new innovation of clay pitcher is called 'Labu Acu' or cast clay pitcher. Researcher found this innovation could produce commercialized products compared to those produced using old ways. It is able to improve the quality and quantity of Labu Sayong to meet market demand. It also means a competition between the latest designs of Labu Sayong with the existing pottery in the market. Cooperation among the entrepreneurs is also formed through a work specialization system to increase productivity. It is hoped that this research will impart the knowledge that Labu Sayong production is already going through innovative transformation to meet customer needs and prevent heritage from disappearing with passing time.